Android Based Dyslexia Early Screening Test - Abu Zarim, Nor Azimah (UTeM, 2016)
Dyslexia is one of the learning disabilities which cannot be identify through physical appearance but need a specific assessment. Parents are not aware about the symptoms until the clinical assessment is carried out. In order to encourage parents to detect the symptoms in the early age, an android based dyslexia early symptom test is designed. The application is simple to use, easy to understand, enjoyable and can motivate children. The test comprise on visual test. It can be apply via smartphone, iPad or tablet. Parents can easily download the application from internet and conduct the test on their children. It will provide immediate score. Thus, parents can bring their children to psychologist for further diagnose and remediation. This is only a first step for parents and school teachers to detect the risks of dyslexia symptom which is very important when children start schooling.